1982
DOI: 10.1007/bf01871588
|View full text |Cite
|
Sign up to set email alerts
|

Ionic regulation of the unicellular green algadunaliella tertiolecta

Abstract: Summary. Different techniques were investigated in order to determine the Na, K and C1 concentrations of Dunaliella tertiolecta cells adapted to a large range of salinity (20 to 1640 mM NaCI). The K cell concentrations were 6 to 13 times higher than the K concentration of the external medium (11 raM). The The Na and C1 cell concentrations, on the other hand, were lower than in the external medium at all salinities tested. Considerable differences in the absolute values of Na and C1 were, however, found accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
1

Year Published

1986
1986
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 26 publications
1
35
1
Order By: Relevance
“…The intracellular concentration of ions can be modified artificially by incubating the cells in the presence of ionophores. Ehrenfeld & Cousin (1982) showed that the antibiotics nystatin (20 yg ml-l) and monensin (5-60 pg ml-l)…”
Section: Introductionmentioning
confidence: 99%
“…The intracellular concentration of ions can be modified artificially by incubating the cells in the presence of ionophores. Ehrenfeld & Cousin (1982) showed that the antibiotics nystatin (20 yg ml-l) and monensin (5-60 pg ml-l)…”
Section: Introductionmentioning
confidence: 99%
“…Changes in Na+ content (6,13) pH level (9), phosphate (8), inositol phospholipids (7), and in ultrastructure (1 1) have been observed following osmotic shocks and were suggested to be involved in triggering glycerol production or elimination.…”
mentioning
confidence: 99%
“…Different groups have determined intracellular Na+ concentrations ranging from around 50% (12,16), to less than 10% (3,6,15) and even to about 1% (8) of the external NaCl concentration. These differences seem to be mainly due to difficulties in effecting a complete separation of the cells from the extracellular Na+; to errors in the determination of intracellular osmotic volumes with different extracellular markers (8,12,14,15) MATERIALS AND METHODS Growth Conditions. D. salina were grown in batch cultures, in media containing 1 to 4 M NaCl, 50 mm NaHCO3, 5 mM KNO3, 5 mM MgSO4, 0.3 mM CaCI2, 0.2 mM KH2PO4, 1.5 /LM FeC13,6 ,uM EDTA, 185 ,uM H3BO4, 7 AM MnC12, 0.8 piM ZnC12, 0.02 AM CoCl2, and 0.2 nm CuCl2.…”
mentioning
confidence: 99%
“…However, there is a considerable disagreement as to the contribution of inorganic ions, in particular for Na+ to the overall osmotic pressure inside the cells. Different groups have determined intracellular Na+ concentrations ranging from around 50% (12,16), to less than 10% (3,6,15) and even to about 1% (8) of the external NaCl concentration. These differences seem to be mainly due to difficulties in effecting a complete separation of the cells from the extracellular Na+; to errors in the determination of intracellular osmotic volumes with different extracellular markers (8,12,14,15); and to possible damage to the cells during the separation technique which may result in ion reequilibrations or losses of internal contents.…”
mentioning
confidence: 99%